2001
DOI: 10.1007/s11741-001-0049-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different surface treatments of H13 hot work die steel on its thermal fatigue behaviors

Abstract: Thermal fatigue checking is the general failure of hot work die steels, which is relative with the structures and properties of the steels and the stress alternated during the employment. The Uddeholm test method on thermal fatigue is used to compare the behaviors of different samples, which are treated with plasma nitriding,plasma sulfur-carbon-nitriding,boronizing or not treated. The results show that the nitriding improves the thermal fatigue property of the tool steel, while the plasma sulfur-carbon-nitrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Various surface treatment techniques are used to create a continuous compound layer and decrease the damage of crack, corrosion and erosion, such as quenching, physical vapour deposition, chemical vapor deposition process, laser cladding, etc. [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Various surface treatment techniques are used to create a continuous compound layer and decrease the damage of crack, corrosion and erosion, such as quenching, physical vapour deposition, chemical vapor deposition process, laser cladding, etc. [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Surface engineering of physical vapor deposition (PVD), nitriding, boronizing, etc. can decrease the damage of corrosion and wear on dies through the formation of the continuous compound layer, serving as effective isolating between the molten metal and dies surface [6][7][8][9][10][11]. Especially a few surface modification technologies are beneficial to improving the thermal fatigue resistance due to the enhanced surface hardness and induced residual compressive stress [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Min [7] and Pellizzari [14] demonstrated that a thinner and compact nitrided compound layer is expected to show the better thermal fatigue resistance behavior. Kundalkar [13] indicated that the thermal fatigue resistance decreased with the increase of phase ratio of ε-Fe2-3N and γ′-Fe4N in the nitrided layers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a comprehensive analysis of the major destructive mechanisms of tools in the forging process of car steering was presented in work [11]. In order to avoid those phenomena, various methods are used, which usually consist in producing or applying appropriate protective layers, the task of which is the protection from one or more destructive mechanisms [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that this method is well-known and well-mastered, it does not always provide a clear effect of durability improvement. That is why other methods are being searched for to improve tool durability in forging processes, which are more effective, yet more expensive as well [12,13]. The most recent methods include undoubtedly hybrid technologies, consisting in the use of two or more surface engineering techniques.…”
Section: Introductionmentioning
confidence: 99%